Yield Responses of Direct-Seeded Wheat to Rhizobacteria and Fungicide Seed Treatments - Cook, R James (Plant disease, 2002)
Field trials were conducted with winter and spring wheat in eastern Washington and northern Idaho over several years to determine the benefit, as measured by grain yield, of seed treatments with rhizobacteria and formulated fungicides in cropping systems favorable to root diseases. The trials were conducted with wheat direct-seeded (no-till) in fields with a history of intensive cereals and one or more of the root diseases: take-all caused by Gaeumannomyces graminis var. tritici, Rhizoctonia root rot caused by Rhizoctonia solani AG8 and R. oryzae, and Pythium root rot caused mainly by Pythium irregulare and P. ultimum. The seed treatments included Bacillus sp. L324-92, Pseudomonas fluorescens Q69c-80, Pseudomonas fluorescens Q8r1-96, difenoconazole + metalaxyl (Dividend + Apron), difenoconazole + mefenoxam (Dividend + Apron XL = Dividend XL), tebuconazole + metalaxyl (Raxil XT), and tebuconazole + thiram (Raxil-thiram). Controls were nontreated seed planted into both nontreated (natural) soil and soil fumigated with methyl bromide just prior to planting. Although the data indicate a trend in higher wheat yields with two rhizobacteria treatments over the nontreated control (171 and 264 kg/ha, respectively), these higher yields were not significantly different from the nontreated control (P = 0.06). Fungicide seed treatments alone similarly resulted in yields that were 100 to 300 kg/ha higher than the nontreated control, but only the yield responses to Dividend on winter wheat (289 kg/ha) and Dividend + Apron on spring wheat (263 kg/ha) were significant (P ≤ 0.05). The greatest yield increases over the nontreated control occurred with certain rhizobacteria-fungicide combinations, with three treatments in the range of 312 to 486 kg/ha (6.1 to 17.7%; P ≤ 0.05). Some rhizobacteria-fungicide combinations brought average yields to within 85 to 90% of those obtained with soil fumigation. Only soil fumigation produced a measurable reduction in the incidence of take-all and Rhizoctonia root rot, as assessed on washed roots. No reliable method exists for visual quantification of Pythium root rot on wheat